A flexible composite material and its preparation method and application
By combining strontium titanate nanomaterials in fiber cloth, the weather resistance of flexible photovoltaic modules is improved, and the problem of insufficient weather resistance in the prior art is solved, and the characteristics of light weight, high strength and high light transmittance of the material are realized. Long-term use in complex roofs and environments.
Patent Information
- Application Number
- CN202310778172.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-06-29
AI Technical Summary
The existing flexible photovoltaic modules are insufficient weather resistance and are difficult to meet the long-term use requirements in complex roof shapes and environments.
Using flexible composite materials including fiber cloth and strontium titanate nanomaterial composites in fiber cloth, the weather resistance of the material is improved through specific ratios of strontium titanate nano additives and other additives, and prepared by melt-infiltrating and curing processes. .
It realizes excellent weather resistance of flexible composite materials, has light weight, high intensity, high light transmittance and water resistance, and is suitable as a packaging material for photovoltaic modules and extends service life.
Smart Images

Figure BDA0004310041500000101 
Figure BDA0004310041500000111 
Figure BDA0004310041500000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional materials, and in particular to a flexible composite material and a preparation method and application thereof. Background Art
[0002] Traditional photovoltaic modules are composed of TPT backboard, EVA film, battery cells, glass panels, frames, etc. Traditional photovoltaic modules are rigid components, not easy to deform, and are relatively heavy, which are not suitable for places that require bending or light weight. Flexible solar panels are emerging technology products in the world's solar energy industry. Specifically, flexible composite materials replace the glass panels and even TPT backboards in traditional photovoltaic modules to protect and support the battery cells. Flexible solar panels are flexible and easy to bend. When the average slope of the roof is <60° and the radius of the bending panel is >13m, they can be bent arbitrarily according to the shape of the roof. Moreover, flexible solar panels are light in weight, and will not cause excessive load on the roof due to the laying of solar panels, and the main structure of the roof will not change significantly due to the laying of solar panels. However, the weather resistance of flexible composite materials in the prior art still needs to be improved. Summary of the invention
[0003] The purpose of the present invention is to provide a flexible composite material and a preparation method and application thereof. The flexible composite material provided by the present invention has excellent weather resistance.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a flexible composite material, comprising a fiber cloth and a strontium titanate nano-micro material composited in the fiber cloth;
[0006] The raw materials for preparing the strontium titanate nanomaterial include a base material and a dispersant, wherein the mass of the dispersant is 0.05-0.2% of the mass of the base material; the base material includes the following raw materials by mass: 50-90 parts of powdered resin; 10-50 parts of curing agent; 0-20 parts of antioxidant; 0.05-0.2 parts of catalyst; 0-10 parts of surface adjuster; 0-20 parts of light stabilizer; 0.05-5 parts of strontium titanate nano-additive, wherein the strontium titanate nano-additive is a mixture of octahedral strontium titanate, hexahedral strontium titanate and irregular strontium titanate, and the mass ratio of the octahedral strontium titanate, the hexahedral strontium titanate and the irregular strontium titanate is 3-4:4-6:1-2.
[0007] Preferably, the fiber cloth is glass fiber cloth.
[0008] Preferably, the fiber cloth has a gram weight of 100 to 400 g / m 2 .
[0009] Preferably, the particle size of the matrix material is 30 to 150 μm; and the particle size of the dispersant is 2 to 8 μm.
[0010] Preferably, the content of strontium titanate nanomaterials in the flexible composite material is 50-80wt%.
[0011] The present invention provides a method for preparing the flexible composite material described in the above technical solution, comprising the following steps:
[0012] The fiber cloth is impregnated with molten strontium titanate nanomaterials and then solidified to obtain a flexible composite material.
[0013] Preferably, the method of using molten strontium titanate nanomaterial to impregnate the fiber cloth comprises the following steps:
[0014] The strontium titanate nano-micro material is laid on the surface of the fiber cloth, and is heated by a laminating device or a rolling device to melt the strontium titanate nano-micro material and infiltrate the fiber cloth.
[0015] Preferably, the method of using molten strontium titanate nanomaterial to impregnate the fiber cloth comprises the following steps:
[0016] The strontium titanate nanomaterial is extruded to obtain a resin film, the resin film is laminated and compounded on the surface of the fiber cloth, and the resin film is heated by a laminating device or a rolling device to melt and infiltrate the fiber cloth.
[0017] Preferably, the curing temperature is 130-200° C., the pressure is 1-20 MPa, and the time is 10-90 min.
[0018] The present invention provides the use of the flexible composite material described in the above technical solution or the flexible composite material prepared by the preparation method described in the above technical solution as a photovoltaic module packaging material.
[0019] Beneficial effects: The flexible composite material provided by the present invention is compounded with strontium titanate nano-materials in the fiber cloth, and a strontium titanate nano-additive is added to the matrix material of the strontium titanate nano-materials, and the strontium titanate nano-additive is obtained by compounding strontium titanate of a specific morphology according to a specific ratio, which can make the flexible composite material have excellent weather resistance; in addition, the flexible composite material provided by the present invention also has the characteristics of light weight, high strength, high light transmittance and good water-blocking performance. DETAILED DESCRIPTION
[0020] The present invention provides a flexible composite material, comprising a fiber cloth and a strontium titanate nano-micro material composited in the fiber cloth;
[0021] The raw materials for preparing the strontium titanate nanomaterial include a base material and a dispersant, wherein the mass of the dispersant is 0.05-0.2% of the mass of the base material; the base material includes the following raw materials by mass: 50-90 parts of powdered resin; 10-50 parts of curing agent; 0-20 parts of antioxidant; 0.05-0.2 parts of catalyst; 0-10 parts of surface adjuster; 0-20 parts of light stabilizer; 0.05-5 parts of strontium titanate nano-additive, wherein the strontium titanate nano-additive is a mixture of octahedral strontium titanate, hexahedral strontium titanate and irregular strontium titanate, and the mass ratio of the octahedral strontium titanate, the hexahedral strontium titanate and the irregular strontium titanate is 3-4:4-6:1-2.
[0022] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.
[0023] The flexible composite material provided by the present invention comprises a fiber cloth. In the present invention, the fiber cloth is preferably a glass fiber cloth, and the glass fiber cloth is preferably a woven glass fiber cloth; the gram weight of the fiber cloth is preferably 100 to 400 g / m 2 , specifically 100g / m 2 , 200g / m 2 , 300g / m 2 or 400g / m 2 The thickness of the flexible composite material of the present invention is mainly affected by the weight of the fiber cloth. Specifically, in the present invention, the thickness of the flexible composite material is preferably 0.1 to 0.4 mm, more preferably 0.15 to 0.31 mm, and specifically can be 0.15 mm, 0.22 mm or 0.31 mm.
[0024] The flexible composite material provided by the present invention includes a strontium titanate nano-micro material compounded in the fiber cloth, and the strontium titanate nano-micro material is specifically impregnated and compounded with the fibers in the fiber cloth. In the present invention, the content of the strontium titanate nano-micro material in the flexible composite material is preferably 50-80wt%, more preferably 51-78wt%, further preferably 52-75wt%, further preferably 53-70wt%, further preferably 54-65wt%, and further preferably 55-60wt%.
[0025] In the present invention, the raw materials for preparing the strontium titanate nanomaterials include a matrix material; in terms of mass fractions, the raw materials for preparing the matrix material include 50 to 90 parts of powdered resin, preferably 55 to 80 parts, more preferably 60 to 78 parts, further preferably 65 to 75 parts, and further preferably 70 to 72 parts. In the present invention, the powdered resin preferably includes one or more of acrylic resin, polyurethane resin and polyester resin, more preferably acrylic resin. The present invention preferably uses acrylic resin as the main material, which has the advantages of good weather resistance, high film-forming strength, excellent impact resistance and excellent flexibility. In the present invention, the acrylic resin is preferably an epoxy acrylic resin, more preferably patent CN 115651473A described epoxy acrylic powder coating resin; specifically, the raw materials of the epoxy acrylic powder coating resin include 20-70 parts of hard monomers, 10-60 parts of soft monomers, 10-50 parts of cross-linking monomers and 0.5-8 parts of initiators; the cross-linking monomers include epoxy-containing monomers and / or hydroxyl-containing monomers; the hard monomers include at least one of methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobornyl methacrylate, dicyclopentadiene acrylate, dicyclopentadiene ethoxy acrylate, styrene, methyl styrene or acrylonitrile; the soft monomers include alkyl acrylate compounds; the epoxy-containing monomers include at least one of glycidyl methacrylate, glycidyl acrylate, hydroxybutyl glycidyl ether or tert-butyl glycidyl ether; The hydroxyl-containing monomer comprises at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, β-hydroxypropyl acrylate, β-hydroxypropyl methacrylate or N-hydroxymethyl acrylamide; the mass ratio of the epoxy-containing monomer to the hydroxyl-containing monomer in the cross-linking monomer is (2-15):1; the epoxy type acrylic powder coating resin is prepared by the following method, which comprises: dripping a mixture of a hard monomer, a soft monomer, a cross-linking monomer, an initiator with a formula amount of 40-50% and an optional molecular weight regulator into a solvent, and after the first reaction, dripping the remaining initiator, continuing the reaction, and obtaining the epoxy type acrylic powder coating resin; the temperature of the first reaction is 80-110° C., the time is 2-4 hours, and the time of the continued reaction is 2-4.5 hours.
[0026] Based on the mass fraction of the powdered resin, the raw materials for preparing the matrix material in the present invention include 10 to 50 parts of a curing agent, preferably 15 to 30 parts, more preferably 18 to 25 parts, and further preferably 20 to 21 parts. In the present invention, the curing agent preferably includes one or more of dodecanediol (DDDA), triglycidyl isocyanurate (TGIC) and isocyanate, more preferably DDDA, TGIC or isocyanate. The present invention preferably uses the above-mentioned types of curing agents, which is beneficial to improving the film-forming efficiency while ensuring the basic physical properties of the film.
[0027] Based on the mass fraction of the powdered resin, the raw materials for preparing the matrix material in the present invention include 0 to 20 parts of antioxidants, preferably 0.3 to 10 parts, more preferably 0.5 to 5 parts, and further preferably 1 to 2 parts. In the present invention, the antioxidant preferably includes one or more of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1076), benzofuranone derivatives and thioesters, more preferably antioxidant 1076. The present invention preferably uses the above-mentioned types of antioxidants, which is beneficial to improving weather resistance.
[0028] Based on the mass fraction of the powdered resin, the raw materials for preparing the matrix material in the present invention include 0.05 to 0.2 parts of catalyst, preferably 0.06 to 0.15 parts, more preferably 0.07 to 0.1 parts, and further preferably 0.075 to 0.085 parts. In the present invention, the catalyst preferably includes tetrabutylammonium bromide, dibutyltin dilaurate or 2-propylimidazole, more preferably tetrabutylammonium bromide. The present invention preferably uses the above-mentioned types of catalysts, which is conducive to improving film forming efficiency.
[0029] Based on the mass fraction of the powdered resin, the raw materials for preparing the matrix material in the present invention include 0 to 10 parts of a surface conditioner, preferably 0.3 to 5 parts, more preferably 0.5 to 2 parts, and further preferably 0.8 to 1 parts. In the present invention, the surface conditioner preferably includes benzoin. The present invention preferably uses the above-mentioned types of surface conditioners, which is beneficial to improving the surface flatness and transmittance after film formation.
[0030] Based on the mass fraction of the powder resin, the raw materials for preparing the matrix material in the present invention include 0 to 20 parts of light stabilizer, preferably 0.5 to 15 parts, more preferably 0.8 to 10 parts, further preferably 1.2 to 7 parts, and further preferably 1.66 to 3 parts. In the present invention, the light stabilizer preferably includes a triazine light stabilizer or a hindered amine light stabilizer, more preferably a triazine light stabilizer; the triazine light stabilizer is preferably 2-[2-hydroxy-4-[3-(2-ethylhexyloxy)-2-hydroxypropoxy]phenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine (light stabilizer UV-405); the hindered amine light stabilizer is preferably one or more of high molecular weight triazine-piperidine condensate (light stabilizer 119), Tinuvin 622 and Tinuvin 770. The present invention preferably uses the above-mentioned types of light stabilizers, which is conducive to improving weather resistance.
[0031] Based on the mass fraction of the powdered resin, the raw materials for preparing the matrix material in the present invention include 0.05 to 5 parts of strontium titanate nano-additive, preferably 0.1 to 4.8 parts, more preferably 0.5 to 4.5 parts, further preferably 1 to 4 parts, further preferably 1.5 to 3.5 parts, and further preferably 2 to 3.45 parts. In the present invention, the strontium titanate nano-additive is a mixture of octahedral strontium titanate, hexahedral strontium titanate and irregular strontium titanate, and the mass ratio of the octahedral strontium titanate, hexahedral strontium titanate and irregular strontium titanate is 3 to 4: 4 to 6: 1 to 2, preferably 3 to 3.5: 5 to 6: 1 to 1.5, and more preferably 3: 6: 1. In the present invention, the particle size of the strontium titanate nano-additive is preferably 50-300nm, more preferably 50-200nm; in the present invention, the particle size of the octahedral strontium titanate is preferably 100-200nm, the particle size (side length) of the hexahedral strontium titanate is preferably 100-200nm, and the particle size of the irregular strontium titanate is preferably 50-100nm. In the present invention, the strontium titanate nano-additive is compounded with strontium titanate of a specific morphology, which can make the strontium titanate nano-micro material have excellent weather resistance; and the compounding of strontium titanate of different morphologies can provide different crystal planes, which is conducive to the efficient separation of photoinduced charges and holes, thereby improving the photoelectric conversion efficiency.
[0032] In the present invention, the raw materials for preparing the strontium titanate nanomaterials include a dispersant, and the dispersant preferably includes one or more of alumina, fumed silica and glass beads, and more preferably alumina. In the present invention, the mass of the dispersant is 0.05-0.2% of the mass of the matrix material, preferably 0.1-0.15%. The present invention preferably uses the above-mentioned types of dispersants, which is beneficial to avoid agglomeration and improve the product processing performance.
[0033] In the present invention, the particle size of the matrix material is preferably 30 to 150 μm; the particle size of the dispersant is preferably 2 to 8 μm, more preferably 2 to 4 μm.
[0034] The present invention provides a method for preparing the strontium titanate nanomaterial described in the above technical solution, comprising the following steps:
[0035] The raw materials for preparing the matrix material are mixed, and the mixture is melt-extruded, cooled, crushed and sieved in sequence to obtain the matrix material; the matrix material is mixed with a dispersant to obtain the strontium titanate nano-micro material;
[0036] Alternatively, the raw materials for preparing the matrix material are mixed with a dispersant, and then melt-extruded, cooled, crushed and sieved in sequence to obtain the strontium titanate nano-micro material.
[0037] In the present invention, different methods can be used to prepare the strontium titanate nanomaterial according to the timing of adding the dispersant, which will be described in detail below.
[0038] The first method: the present invention mixes the raw materials for preparing the matrix material, and sequentially melts and extrude, cools, crushes and sieves to obtain the matrix material; the matrix material is mixed with a dispersant to obtain the strontium titanate nano-micro material. In the present invention, the mixing method of the raw materials for preparing the matrix material is preferably mechanical mixing. The present invention has no special restrictions on the conditions for the mechanical mixing, and it is sufficient to ensure that the raw materials are mixed evenly. In the present invention, the temperature of the melt extrusion is preferably 90-130°C, and more preferably 110-120°C. The present invention has no special restrictions on the cooling, and a cooling method familiar to those skilled in the art can be used. In the present invention, the crushing preferably includes first crushing and second crushing in sequence; the first crushing preferably crushes the material to a particle size of 0.2-1cm; the second crushing preferably crushes the material to a particle size of 30-150μm. The present invention has no special restrictions on the screening, and it is sufficient to obtain a matrix material of the desired particle size. In the present invention, the mixing method of the matrix material and the dispersant is preferably mechanical mixing. The present invention has no special restrictions on the conditions for the mechanical mixing, and it is sufficient to ensure that the matrix material and the dispersant are mixed evenly.
[0039] The second method: The present invention mixes the raw materials for preparing the matrix material with a dispersant, and sequentially melt-extrudes, cools, crushes and screens to obtain the strontium titanate nanomaterial. In the present invention, the raw materials for preparing the matrix material and the dispersant are preferably mixed mechanically. The present invention does not specifically limit the conditions for the mechanical mixing, as long as the raw materials are mixed evenly. In the present invention, the specific operations of melt extrusion, cooling, crushing and screening involved in the second method are preferably consistent with the specific operations of melt extrusion, cooling, crushing and screening involved in the first method, and will not be repeated here.
[0040] The present invention provides a method for preparing the flexible composite material described in the above technical solution, comprising the following steps:
[0041] The fiber cloth is impregnated with molten strontium titanate nanomaterials and then solidified to obtain a flexible composite material.
[0042] The present invention can use different methods to impregnate the fiber cloth with the molten strontium titanate nanomaterial, which will be specifically described below.
[0043] The first method is: laying the strontium titanate nano-micro material on the surface of the fiber cloth, and heating the strontium titanate nano-micro material through a laminating device or a rolling device to melt the strontium titanate nano-micro material and impregnate the fiber cloth. The present invention preferably uses a powdering device to evenly sprinkle the strontium titanate nano-micro material on the surface of the fiber cloth, and then the fiber cloth with the strontium titanate nano-micro material sprinkled on the surface is loaded into the laminating device, and the mold is closed and heated to melt the strontium titanate nano-micro material and impregnate the fiber cloth; or a rolling device is used to roll and heat the fiber cloth with the strontium titanate nano-micro material sprinkled on the surface to melt the strontium titanate nano-micro material and impregnate the fiber cloth. The present invention uses a rolling device to facilitate continuous production. In the present invention, the powdering speed of the powdering device is preferably 1 to 10 m / min, more preferably 2 to 6 m / min, and further preferably 3 to 4 m / min. In the present invention, the heating temperature is based on ensuring the melting of the strontium titanate nanomaterial. Specifically, the heating temperature is preferably 130-170°C, more preferably 130-160°C, and further preferably 130-150°C.
[0044] The second method is to extrude the strontium titanate nanomaterial to obtain a resin film, laminate the resin film on the surface of the fiber cloth, and heat the resin film through a laminating device or a rolling device to melt and impregnate the fiber cloth. The present invention preferably uses an extrusion device to extrude the strontium titanate nanomaterial to obtain a resin film, laminate the resin film on the surface of the fiber cloth, and then use a rolling device to roll and heat the fiber cloth composited with the resin film to melt the resin film and impregnate the fiber cloth with the molten strontium titanate nanomaterial. The present invention uses a rolling device to facilitate continuous production. In the present invention, the extrusion speed of the extrusion device is preferably 1 to 10 m / min, and more preferably 1 to 6 m / min. In the present invention, the heating temperature is based on ensuring that the resin film is melted. Specifically, the heating temperature is preferably 130 to 170°C, more preferably 130 to 160°C, and further preferably 130 to 150°C.
[0045] After the fiber cloth is impregnated with molten strontium titanate nanomaterial, the present invention solidifies the obtained material to obtain a flexible composite material. In the present invention, the curing temperature is preferably 130-200°C, more preferably 140-170°C, and further preferably 150-160°C; the pressure is preferably 1-20MPa, more preferably 5-15MPa, and further preferably 8-10MPa; the time is preferably 10-90min, more preferably 20-60min, and further preferably 30-40min. In the present invention, when a laminating device is used to prepare the flexible composite material, the curing is preferably followed by cooling and demolding to obtain a flexible composite material; when a rolling device is used to prepare the flexible composite material, the curing is preferably followed by rolling or cutting into the desired size to obtain a flexible composite material.
[0046] The present invention provides the use of the flexible composite material described in the above technical solution or the flexible composite material prepared by the preparation method described in the above technical solution as a photovoltaic module packaging material. In the present invention, the photovoltaic module is preferably a lightweight photovoltaic module. In the present invention, the packaging material can be specifically used for the front panel of the photovoltaic module, and can also be used for the back panel of the photovoltaic module.
[0047] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] The strontium titanate nano-additive used in the examples of the present invention is the product prepared in Preparation Examples 1 to 3.
[0049] Preparation Example 1
[0050] The steps for preparing hexahedral strontium titanate nanoparticles are as follows:
[0051] Mixing palmitic acid, ethylene glycol, 1,2-butanediol and water to obtain a composite morphology regulator, wherein the concentration of palmitic acid in the composite morphology regulator is 0.2wt%, the concentration of ethylene glycol is 0.2wt%, and the concentration of 1,2-butanediol is 2wt%; dropping a titanium tetrachloride aqueous solution with a concentration of 0.003g / mL into the composite morphology regulator, and the volume ratio of the composite morphology regulator to the titanium tetrachloride aqueous solution is 1:2, stirring for 30 minutes, and cooling with ice water during the stirring process to obtain a mixed solution I;
[0052] The mixed solution I, a lithium hydroxide aqueous solution with a concentration of 0.033 g / mL, and a strontium hydroxide aqueous solution with a concentration of 0.01 g / mL were mixed in a volume ratio of 3:3:1, and stirred for 15 minutes to obtain a mixed solution II with a pH value of 13.8;
[0053] The mixed solution II was heated to 180°C at a heating rate of 4°C / min for hydrothermal reaction for 48 hours, and then cooled at a cooling rate of 2°C / min. The material after the hydrothermal reaction was centrifuged, and the precipitate was washed alternately with water and ethanol for 5 times, and finally dried at 90°C for 4 hours to obtain hexahedral strontium titanate nanoparticles.
[0054] Preparation Example 2
[0055] The steps for preparing octahedral strontium titanate nanoparticles are as follows:
[0056] Mixing palmitic acid, ethylene glycol, 1,2-butanediol and water to obtain a composite morphology regulator, wherein the concentration of palmitic acid in the composite morphology regulator is 0.2wt%, the concentration of ethylene glycol is 1wt%, and the concentration of 1,2-butanediol is 0.2wt%; dropping a titanium tetrachloride aqueous solution with a concentration of 0.003g / mL into the composite morphology regulator, and the volume ratio of the composite morphology regulator to the titanium tetrachloride aqueous solution is 1:2, stirring for 30 minutes, and cooling with ice water during the stirring process to obtain a mixed solution I;
[0057] The mixed solution I, a sodium hydroxide aqueous solution with a concentration of 0.033 g / mL, and a strontium chloride hexahydrate aqueous solution with a concentration of 0.01 g / mL were mixed in a volume ratio of 3:3:1, and stirred for 30 minutes to obtain a mixed solution II with a pH value of 14.2;
[0058] The mixed solution II was heated to 190°C at a heating rate of 4°C / min for a hydrothermal reaction for 24 hours, and then cooled at a cooling rate of 2°C / min. The material after the hydrothermal reaction was centrifuged, and the precipitate was washed alternately with water and ethanol for 3 times, and finally dried at 80°C for 6 hours to obtain octahedral strontium titanate nanoparticles.
[0059] Preparation Example 3
[0060] The steps for preparing irregular strontium titanate are as follows:
[0061] Mixing palmitic acid, ethylene glycol, 1,2-butanediol and water to obtain a composite morphology regulator, wherein the concentration of palmitic acid in the composite morphology regulator is 0.2wt%, the concentration of ethylene glycol is 1.2wt%, and the concentration of 1,2-butanediol is 1.6wt%; dropping a titanium tetrachloride aqueous solution with a concentration of 0.003g / mL into the composite morphology regulator, and the volume ratio of the composite morphology regulator to the titanium tetrachloride aqueous solution is 1:2, stirring for 30min, and cooling with ice water during the stirring process to obtain a mixed solution I;
[0062] The mixed solution I, a sodium hydroxide aqueous solution with a concentration of 0.033 g / mL, and a strontium chloride hexahydrate aqueous solution with a concentration of 0.01 g / mL were mixed in a volume ratio of 3:3:1, and stirred for 30 minutes to obtain a mixed solution II with a pH value of 14.2;
[0063] The mixed solution II was heated to 180°C at a heating rate of 4°C / min for a hydrothermal reaction for 72 hours, and then cooled at a cooling rate of 2°C / min. The material after the hydrothermal reaction was centrifuged, and the precipitate was washed alternately with water and ethanol for 5 times, and finally dried at 80°C for 6 hours to obtain irregular strontium titanate nanoparticles.
[0064] Example 1
[0065] In this embodiment, the raw materials for preparing strontium titanate nanomaterials include a base material and a dispersant;
[0066] 72 parts of acrylic resin (specifically, the epoxy acrylic powder coating resin prepared in Example 7 of patent CN 115651473 A), 21 parts of curing agent (specifically, DDDA), 1 part of antioxidant (specifically, antioxidant 1076), 0.085 parts of catalyst (specifically, tetrabutylammonium bromide), 0.8 parts of surface adjuster (specifically, benzoin), 1.66 parts of light stabilizer (specifically, light stabilizer UV-405) and 3.45 parts of strontium titanate nano-additive (specifically, octahedral strontium titanate, hexahedral strontium titanate and irregular strontium titanate are mixed in a mass ratio of 3:6:1) are mixed, melt-extruded at 120° C., the obtained extrudate is cooled and crushed to a particle size of 0.2 to 1 cm, and then further crushed and graded and sieved to obtain a matrix material with a particle size of 30 to 150 μm;
[0067] The dispersant is aluminum oxide, and the particle size of the dispersant is 2 to 4 μm; the mass of the dispersant is 0.1% of the mass of the base material;
[0068] The matrix material is mixed with a dispersant to obtain strontium titanate nanomaterials.
[0069] Use powder spreading equipment to evenly spread strontium titanate nano-micro materials on glass fiber cloth (specifically woven glass fiber cloth with a gram weight of 100g / m 2 ) at a powder sprinkling speed of 4 m / min, loading a glass fiber cloth with strontium titanate nanomaterials on the surface into a laminating device, closing the mold and heating to a temperature of 130°C to melt the strontium titanate nanomaterials and impregnate the glass fiber cloth, and then curing at a temperature of 160°C and a pressure of 10 MPa for 30 minutes. After curing, cooling and demolding are performed to obtain a flexible composite material; the content of strontium titanate nanomaterials in the flexible composite material is 55wt%, and the thickness of the flexible composite material is 0.15mm.
[0070] Example 2
[0071] A flexible composite material was prepared according to the method of Example 1, except that the weight of the glass fiber cloth used was 200 g / m 2 , the thickness of the flexible composite material is 0.22 mm.
[0072] Example 3
[0073] A flexible composite material was prepared according to the method of Example 1, except that the weight of the glass fiber cloth used was 300 g / m 2 , the thickness of the flexible composite material is 0.31 mm.
[0074] Example 4
[0075] A flexible composite material was prepared according to the method of Example 1, except that the content of strontium titanate nanomaterial in the flexible composite material was 60 wt %.
[0076] Comparative Example 1
[0077] The flexible composite material was prepared according to the method of Example 1, except that the strontium titanate nano-additive in the strontium titanate nano-material was omitted.
[0078] Test Example 1
[0079] The strength of the flexible composite materials prepared in Examples 1 to 4 and Comparative Example 1 was tested according to the method of GB / T 13542.2-2021 (the product strength requirement is ≥100 MPa), and the water permeability of the flexible composite materials prepared in Examples 1 to 4 and Comparative Example 1 was tested according to the method of GB / T 21529-2008 (the product water permeability requirement is ≤1.5 g / (m 2 ·24h)), the results are shown in Table 1.
[0080] Table 1 Performance test results of the flexible composite materials prepared in Examples 1 to 4 and Comparative Example 1
[0081]
[0082] It can be seen from Examples 1 to 3 in Table 1 that the greater the gram weight of the glass fiber cloth, the thicker the prepared flexible composite material, the greater its tensile strength, and the higher its water permeability. It can be seen from Examples 1 and 4 that as the content of strontium titanate nanomaterials in the flexible composite material increases, the strength of the flexible composite material will decrease and the water permeability will decrease slightly. It can be seen from Example 1 and Comparative Example 1 that by omitting the strontium titanate nano-additive in the strontium titanate nanomaterial, the strength and water permeability of the flexible composite material do not change much, which shows that adding strontium titanate nanomaterials when preparing the flexible composite material can still enable the flexible composite material to maintain good mechanical properties and water barrier properties.
[0083] Comparative Example 2
[0084] A flexible composite material was prepared according to the method of Example 1, except that the strontium titanate nanomaterial was replaced by a commercially available flexible photovoltaic material.
[0085] Test Example 2
[0086] The elongation at break and light transmittance of the flexible composite materials prepared in Example 1 and Comparative Example 2 were tested and compared with the traditional photovoltaic glass, wherein the elongation at break was tested according to the GB / T 13542.2-2021 method, and the light transmittance was tested according to the GB / T 2410-2008 method, and the results are shown in Table 2. As can be seen from Table 2, although the light transmittance of the flexible composite material prepared using strontium titanate nanomaterials is not as good as that of the traditional photovoltaic glass, the elongation at break and light transmittance are better than those of the flexible composite material prepared from the commercially available flexible photovoltaic material, and the elongation at break is also better than that of the traditional photovoltaic glass.
[0087] Table 2 Performance test results of flexible composite materials and photovoltaic glass prepared in Example 1 and Comparative Example 2
[0088] Sources Elongation at break (%) Light transmittance (%) Example 1 16 90.0 Comparative Example 2 15 86.5 Traditional photovoltaic glass 1.3 91.0
[0089] Test Example 3
[0090] The weather resistance of the flexible composite materials prepared in Example 1 and Comparative Examples 1 to 2 was tested according to the GB / T 29848-2018 method, and the results are shown in Table 3. As can be seen from Table 3, the flexible composite material prepared in Example 1 of the present invention is compounded with strontium titanate nano-micro materials in the fiber cloth, and strontium titanate nano-additives are added to the matrix material of the strontium titanate nano-micro materials, so that the flexible composite material has excellent weather resistance, such as UV resistance and moisture and heat resistance, which are better than the flexible composite materials prepared in Comparative Examples 1 and 2.
[0091] Table 3 Performance test results of the flexible composite materials prepared in Example 1 and Comparative Examples 1-2
[0092]
[0093]
[0094] It can be seen from the above test examples that the flexible composite material provided by the present invention has excellent weather resistance, and also has the characteristics of light weight, high strength, high light transmittance and good water barrier performance; in addition, the flexible composite material provided by the present invention has the characteristics of high anti-fouling and easy cleaning, and the main dirt can usually be removed by washing with rainwater, and the expected outdoor service life is more than 25 years.
[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A flexible composite material, comprising a fiber cloth and a strontium titanate nanomaterial composited in the fiber cloth; The raw materials for preparing the strontium titanate nano-micro material include a base material and a dispersant, wherein the mass of the dispersant is 0.05-0.2% of the mass of the base material; the base material includes the following raw materials by mass: 50-90 parts of powdered resin; 10-50 parts of curing agent; 0-20 parts of antioxidant; 0.05-0.2 parts of catalyst; 0-10 parts of surface adjuster; 0-20 parts of light stabilizer; 0.05-5 parts of strontium titanate nano-additive, wherein the strontium titanate nano-additive is a mixture of octahedral strontium titanate, hexahedral strontium titanate and irregular strontium titanate, wherein the mass ratio of the octahedral strontium titanate, the hexahedral strontium titanate and the irregular strontium titanate is 3-4:4-6:1-2; the particle size of the strontium titanate nano-additive is 50-300nm; The dispersant includes one or more of alumina, fumed silica and glass microspheres, and the particle size of the dispersant is 2 to 8 μm.
2. The flexible composite material according to claim 1, characterized in that: The fiber cloth is glass fiber cloth.
3. The flexible composite material according to claim 2, characterized in that: The fiber cloth has a gram weight of 100 to 400 g / m 2 .
4. The flexible composite material according to claim 1, characterized in that: The particle size of the matrix material is 30 to 150 μm.
5. The flexible composite material according to any one of claims 1 to 4, characterized in that: The content of strontium titanate nanomaterials in the flexible composite material is 50-80wt%.
6. The method for preparing the flexible composite material according to any one of claims 1 to 5, comprising the following steps: The fiber cloth is impregnated with molten strontium titanate nanomaterials and then solidified to obtain a flexible composite material.
7. The preparation method according to claim 6, characterized in that: The method of using molten strontium titanate nano-material to impregnate the fiber cloth comprises the following steps: The strontium titanate nano-micro material is laid on the surface of the fiber cloth, and is heated by a laminating device or a rolling device to melt the strontium titanate nano-micro material and infiltrate the fiber cloth.
8. The preparation method according to claim 6, characterized in that: The method of using molten strontium titanate nano-material to impregnate the fiber cloth comprises the following steps: The strontium titanate nanomaterial is extruded to obtain a resin film, the resin film is laminated and compounded on the surface of the fiber cloth, and the resin film is heated by a laminating device or a rolling device to melt and infiltrate the fiber cloth.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The curing temperature is 130-200° C., the pressure is 1-20 MPa, and the curing time is 10-90 minutes.
10. Use of the flexible composite material according to any one of claims 1 to 5 or the flexible composite material prepared by the preparation method according to any one of claims 6 to 9 as a front panel or back panel of a photovoltaic module.
Citation Information
Patent Citations
High-efficiency protective composite plate and preparation method, application and application method thereof
CN110629557A
Cited By
Flexible composite material and preparation method and application thereof
EP4737118A1
Flexible composite material and preparation method and application thereof
WO2025000930A1